Electoral volatility of the 2019 presidential election: A study in Jakarta and Depok, Indonesia - Aryo Wasisto (Faculty of Social and Political Science, Universitas Airlangga, 2021)
In democratic countries around the world, electoral volatility is a challenge for political actors. Because one vote is significant, political parties and candidates are increasingly difficult to predict the preferences of citizens. This study aimed to analyze motivational factors that make voters change their choice of votes. This study employed a quantitative method and proposed three variables, including political sophistication, candidate evaluation, and exposure to media campaigns. The results of the logistic regression show that voters who positively evaluate candidates become loyal voters (p-value £ 0.001). Meanwhile, voters who consume political information from social media and the internet intensively, as well as those who are interested in politics are non-volatile voters (p-value £ 0.001 and p-value £ 0.01, respectively). These findings contrast with studies in parliamentary countries where interest in politics motivates voters to change their votes. In these analyzes, this study focuses on examining the inter-election volatility of 2014-2019 in the context of the presidential election in Indonesia. The data were obtained from a post-2019 election survey (non-probability sampling), for respondents in South Jakarta, East Jakarta, and Depok City, who had elected the president in the 2014 and 2019 elections.